Optimasi Penyerapan Panas Memanfaatkan Energi Matahari pada Kolektor - M. Iqbal A.P.; Ahmad Syuhada; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2012)
Solar energy is a renewable energy that can be utilized for human needs for various purposes such as electricity, heating, hair, and so forth. Solar collector is a device that collects solar energy and converts it into thermal energy and redirects the energy back into the fluid. Three variations of barrier angle were prepared in order to optimize the absorption of solar energy in a collector. Multiple pass turn were utilized to maximize the heat absorption. The size of the collector is 250 cm × 85 cm. Each side of absober box is coated with aluminum of 10 mm thick. Iron sand is used as absorber with thickness of 6 m. The collector box is tilted with 15° angle. Measurements were carried out for each multiple pass turn angle ; 130°, 180° and 90°. The tests were carried out in an open field in front of the Faculty of Engineering, Syiah Kuala University. The results show that temperature tends to be similar for all three variations of barrier angle. For the barrier angle of 130°, the highest temperature achieved was 93.3°C during 12:00 to 13:00 pm. The highest temperature achieved for the other two variations are 91.2°C for the barrier angle of 90° and 90.2°C for the barrier angle of 180°.